Phase diagrams of a Potts Model with competing binary and ternary interactions - Temir, Seyit; Ganikhodjaev, Nasir; Akin, Hasan; Uguz, Selman (American Institute of Physics, 2010)
The Potts model on the Cayley tree of second order, with competing interactions between the nearest-neighbor, prolonged next-nearest neighbor and two-level triple neighbors has been studied. The phase diagram is studied for several ranges of the competing parameters showing the appearance of several features and modulated phases arising from the frustration effects introduced by the two-level triple neighbors interaction.